The Texas Landscape Project : Nature and People - Todd, David, 1959- (Book collections on Project MUSE., 2016)
The Texas Landscape Project explores conservation and ecology in Texas by presenting a highly visual and deeply researched view of the widespread changes that have affected the state as its population and economy have boomed and as Texans have worked ever harder to safeguard its bountiful but limited natural resources. Covering the entire state, from Pineywoods bottomlands and Panhandle playas to Hill Country springs and Big Bend canyons, the project examines a host of familiar and not so familiar environmental issues. A companion volume to The Texas Legacy Project, this book tracks specific e.